calculati:
a)-13+(-2-3)=
b)(-4+7)-(-2-3)+(-6+1)
Răspunsuri la întrebare
Răspuns de
18
a)-13+(-2-3)
=-13+(-5)=
=-13-5=
=-18
b)(-4+7)-(-2-3)+(-6+1)=
=3-(-5)+(-5)=
=3+5-5=
=3(deoarece -5 cu +5 se reduc)
=-13+(-5)=
=-13-5=
=-18
b)(-4+7)-(-2-3)+(-6+1)=
=3-(-5)+(-5)=
=3+5-5=
=3(deoarece -5 cu +5 se reduc)
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă
Engleza,
10 ani în urmă
Engleza,
10 ani în urmă